Exploring Pretreatment Expectancies in a Campus Mental Health Setting: The Validation of a Novel Expectancies Measure. Issue 1 (April 2014) - Aubuchon‐Endsley, Nicki L.; Callahan, Jennifer L.
<x xml:space="preserve">Abstract</x> Treatment expectancies and outcome have been robustly associated, although these constructs are understudied within college mental health populations. This is partially because of the lack of psychometrically sound expectancy measures for campus clinics. This study examined the validity, reliability, and clinical utility of a novel expectancy measure developed for use in campus clinics. The measure was found to have sound psychometric properties and may prospectively identify pretreatment expectancies that adversely affect treatment outcomes.